Comprehensive economic and social analysis of domestic agriculture - Kelemen, Réka; Káposzta, József; Lőrinc, Balázs (Studia Mundi – Economica, 2023)
Nowadays, both globally and locally, agriculture is receiving a lot of attention, as it is, among other things, the main arena for food production. In recent years and decades, there has been a marked increase in the importance of producing food of sufficient quality and quantity for the population within national borders and of promoting all segments of farming, while the importance of generational change and improving declining agricultural employment is also unquestionable. In conclusion, it is essential to keep the primary sector under constant review, as quantifiable changes in this sector have a major impact on the country's economic situation. Without it, it is impossible to formulate a truly applicable development strategy, whether at local, regional, civil society or policy level. In close connection with this, a number of excellent studies have been published on the importance of the agriculture, forestry and fisheries sectors, but we believe it is worthwhile to examine the agriculture, forestry and fisheries (TE-ÁOR-08: A) sector in Hungary on the basis of a relevant set of indicators, with the aim of exploring new social, economic, infrastructural and spatial economic connections, all in the spirit of examining territorial competitiveness.
Keywords: Hungary; agriculture; regional differences; economic development